2010
DOI: 10.1111/j.1479-828x.2009.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of duration of sexual cohabitation on the risk of hypertension in nulliparous parturients in Ibadan: A cohort study

Abstract: It was concluded that increased length of sexual cohabitation prior to conception reduces the risk of gestational hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
3
9
2
Order By: Relevance
“…It is worth noting that 32.6% of our study cohort reported past history of miscarriage. The proportion of pregnant women with this past pregnancy event was similar to the 29.64% documented in a previous study in South Western Nigeria15. Our data showed that previous history of abortion/miscarriage did not significantly affect the risk of developing pre-eclampsia (Table 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is worth noting that 32.6% of our study cohort reported past history of miscarriage. The proportion of pregnant women with this past pregnancy event was similar to the 29.64% documented in a previous study in South Western Nigeria15. Our data showed that previous history of abortion/miscarriage did not significantly affect the risk of developing pre-eclampsia (Table 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
“…Our data showed that previous history of abortion/miscarriage did not significantly affect the risk of developing pre-eclampsia (Table 2 and 3). Similar findings have been reported in Nigeria15, with previous history of abortion having no significant effect on the hazard of pre-eclampsia (HR=1.05, 95% CI: 0.82–1.35). However, sub-group analysis showed same paternity abortion had a significant protective effect (HR=0.71, 95% CI: 0.55–0.93) on pre-eclampsia15.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The data obtained on those studies was based on personal questionnaires that may not reflect accurately the true sperm exposure. 1,7 Pregnancies following single SD are another example for lack of exposure to the sperm before pregnancy. Donor insemination has been related to hypertensive disorder and other pregnancy complication such as increased cesarean delivery rate, 23 but this association has not been consistent in other studies that showed similar perinatal outcomes in donor versus nondonor sperm cycles.…”
Section: Discussionmentioning
confidence: 99%